Understanding the Unlawful Acts (Problems and Challenges) A Book Review ‘Perbuatan Melanggar Hukum’, Prof. Dr. R. Wirjono Prodjodikoro, SH., CV Mandar Maju, Bandung, 108 Pages, ISBN 978-979-538-470-0 - Nababan, Natanael Andra Jaya (Faculty of Law, Universitas Negeri Semarang, 2020)
Book witen by Prof Dr. R. Wirjono Prodjodikoro, Wirjono was bor in Surakarta, Dutch East Indies, on 15 June 1903. After completing his primary education, he attended the Rechtsschool I in Batavia, graduating in 1922. He then became a judge, later taking time to study at Leiden University in Leiden, Netherlands. This book talks about acts that can violate laws which are viewed from the point of civil law. I The term